The Trajectory of the (η5-Cyclopentadienyl)cobalt-Mediated Cycloisomerization of Ene-Yne-Ene-Type Allyl Propargylic Ethers to Furans: A DFT Appraisal - Wong, Jonathan J.; Chen, Xiangyang; Houk, Kendall N.; Vollhardt, K. Peter C. (Synthesis, 2021)
The mechanisms by which the complexes CpCoL2 (Cp = C5H5; L = CO or CH2=CH2) mediate the cycloisomerizations of α,δ,ω-enynenes containing allylic ether linkages are probed by DFT methods. The outcomes corroborate experimental results and provide energetic and structural details of the trajectories leading to 3-(oxacyclopentyl or cycloalkyl)furans via the intermediacy of isolable CpCo-η4-dienes. They comprise initial stereoselective complexation of one of the double bonds and the triple bond, rate-determining oxidative coupling to a triplet 16e cobalta-2-cyclopentene, and terminal double bond docking, followed by stereocontrolled insertion to assemble intermediate cis- and trans-fused triplet cobalta-4-cycloheptenes. A common indicator of the energetic facility of the latter is the extent of parallel alignment of the alkene moiety and its target Co–Cα bond. The cobalta-4-cycloheptenes transform further by β-hydride elimination–reductive elimination to furnish CpCo-η4-dienes, which are sufficiently kinetically protected to allow for their experimental observation. The cascade continues through cobalt-mediated hydride shifts and dissociation of the aromatic furan ring. The findings in silico with respect to the stereo-, regio-, and chemoselectivity are in consonance with those obtained in vitro.
Keywords: DFT; enynes; β-hydride elimination; cobalt; cycloisomerization; furans